Off‐road vehicles affect nesting behaviour and reproductive success of American Oystercatchers Haematopus palliatus. (11th March 2016) - Borneman, Tracy E.; Rose, Eli T.; Simons, Theodore R.
Abstract : As human populations and associated development increase, interactions between humans and wildlife are occurring with greater frequency. The effects of these interactions, particularly on species whose populations are declining, are of great interest to ecologists, conservationists, land managers and natural resource policy‐makers. The American Oystercatcher Haematopus palliatus, a species of conservation concern in the USA, nests on coastal beaches subject to various forms of anthropogenic disturbance, including aircraft overflights, off‐road vehicles and pedestrians. This study assessed the effects of these human disturbances on the incubation behaviour and reproductive success of nesting American Oystercatchers at Cape Lookout National Seashore, on the Atlantic coast of the USA. We expanded on‐going monitoring of Oystercatchers at Cape Lookout National Seashore by supplementing periodic visual observations with continuous 24‐h video and audio recording at nests. Aircraft overflights were not associated with changes in Oystercatcher incubation behaviour, and we found no evidence that aircraft overflights influenced Oystercatcher reproductive success. However, Oystercatchers were on their nests significantly less often during off‐road vehicle and pedestrian events than they were during control periods before the events, and an increase in the number of off‐road vehicles passing a nest during incubation was consistently associated with significant reductions in daily nest survival (6% decrease in daily nest survival for a one‐vehicle increase in the average number of vehicles passing a nest each day; odds ratio = 0.94; 95% confidence interval (CI) 0.90, 0.98) and hatching success (12% decrease in hatching success for a one‐vehicle increase in the average number of vehicles passing a nest each day; odds ratio = 0.88; 95% CI 0.76, 0.97). Management of vehicles and pedestrians in areas of Oystercatcher breeding is important for the conservation of American Oystercatchers.